Da ética marxista à psicologia vigotskiana: apontamentos para uma síntese - Sartini, Bruno Corrêa (2021)
Ethics appears as a discipline that seeks to explain the various moral behaviors, that is, those behaviors, values, principles that regulate life in our society and that are appropriated by human beings in the most intimate way possible. This research, based on Historical-Cultural Psychology, looks for possible relations between the theoretical formulations made from the Marxist Ethics and the Psychology proposed by Vigotski. The objective was to point out the main elements that make it possible to achieve a synthesis between Marxist ethics and Vigotskian psychology. This work proposed to carry out a theoretical synthesis and for that we used classic texts of Marxist ethics and some texts chosen from the more mature phase of Vygotsky's theoretical development (1930-1934). We perceive a concern in his initial texts for moral behavior; in these Vygotsky already demonstrates having found the sociogenesis of moral values. We also found that the elements worked on by the author on this theme in his first texts and works are incorporated in his work and make up part of his analyzes of human development, especially when discussing the periodization of this development. Thus, we found in Vigotski some theoretical formulations on the process of appropriation of moral norms, that is, it is possible to speak of a moral development from Vigotski, which opens the way for a greater understanding about the development of personality.